2003
DOI: 10.1051/0004-6361:20021837
|View full text |Cite
|
Sign up to set email alerts
|

The Small Magellanic Cloud in the far infrared

Abstract: Abstract. The ISOPHOT experiment onboard the ISO satellite generated a complete view of the Small Magellanic Cloud (SMC) at 170 µm with 1.5 arcmin resolution. The map is analysed using an automated photometry program enabling accurate photometric characterization of the far infrared (FIR) emitting regions. An integrated FIR luminosity of 8.5×10 7 L is obtained, leading to a star formation rate of SFR FIR = 0.015 M /yr. With an average dust temperature of < T D, 170/100 = 20.5 K >, the total dust mass follows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Schwering & Israel (1989) however detected a FIR source at about 1 off the peak opacity coordinates. Wilke et al (2003) re-examined the HiRes 60 -and 100 µm IRAS maps of the region and found a cold FIR source, with an estimated dust temperature of T d ≈ 30 K, just 30 off the CO peak.…”
Section: Sample Cloudsmentioning
confidence: 99%
“…Schwering & Israel (1989) however detected a FIR source at about 1 off the peak opacity coordinates. Wilke et al (2003) re-examined the HiRes 60 -and 100 µm IRAS maps of the region and found a cold FIR source, with an estimated dust temperature of T d ≈ 30 K, just 30 off the CO peak.…”
Section: Sample Cloudsmentioning
confidence: 99%
“…However, the peak of the spectral energy distribution (SED) from cold dust, lying at the long far-infrared (FIR) wavelengths, is outside the wavelength coverage of IRAS, and thus has not been readily accessible until recently. With a wavelength coverage extending to 240 µm and a superior intrinsic sensitivity as compared to IRAS, the ISOPHOT instrument on board ISO (Kessler et al 1996) was the first to directly measure the peak of the FIR SED for a number of nearby galaxies (Tuffs et al 1996 for NGC 6946; Haas et al 1998 for M 31;Wilke et al 2003 for the SMC, Hippelein et al 2003 for M 33), for smaller statistical samples (Krügel et al 1998;Siebenmorgen et al 1999;Contursi et al 2001), for serendipitously detected spirals (Stickel et al 2000), for the ISOPHOT Virgo Cluster Deep Sample (Tuffs et al 2002a,b;Popescu et al 2002;) and for the sample of Bright Revised Shapley Ames galaxies (Bendo et al 2002(Bendo et al , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…In Wilke et al (2003) (Paper I hereafter), a map of the Small Magellanic Cloud (SMC) obtained with ISOPHOT in the new 170 µm wavelength band was presented. In order to treat the ISO and IRAS data in an identical and reproducible way we obtained IRAS high resolution maps at 12, 25, 60 and 100 µm by requesting HiRes processing at IPAC.…”
Section: Introductionmentioning
confidence: 99%